PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PENINGKATAN KINERJA KARYAWAN DI PT. BUANA HIJAU ABADI - Tira, Yani Tia; Astikawati, Yunita; Pelipa, Emilia Dewiwati; Giovanni, Jonathan (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This research aims to examine compensation for employee performance, motivation for employee performance. This research uses quantitative methods. The data analysis technique in this research is multiple linear analysis, instrument testing, classical assumption testing (normality, heteroscedasticity and multicollinearity tests, coefficient of determination test and hypothesis testing. The population in this research is taking 30 employees who work at PT. Buana Hijau Abadi using primary data using saturated sampling, a sample of 30 respondents was obtained, processing the data using SPSS version 29 software. The results of this research show that compensation (X1) in the t test has no influence on employee performance (Y). This is proven by the calculated t value > t table is (0.129 > 0.05) and motivation (X2) there is an influence of motivation on performance (Y). This is proven by the calculated t value < t table with a value of (0.007 < 0.05, but in the F Compensation statistical test and Motivation have a simultaneous influence on employee performance, this is proven by the calculated t value < t table (0.004 < 0.05). The Adjusted R Square coefficient of determination of 3.34 states that the Compensation (X1) and Motivation (X2) variables have contribution is 33.4% to employee performance (Y) and the remaining 66.6% is influenced by other factors.